PENGELOLAAN LINGKUNGAN DAN BUDAYA SEKOLAH SERTA DAMPAKNYA TERHADAP DISIPLIN KERJA GURU SEKOLAH LUAR BIASA NEGERI (SLBN) DI KABUPATEN KUNINGAN - Tarsim; Ipong Dekawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The work discipline of teachers at State Special Schools in Kuningan Regency is considered suboptimal. Based on initial observations, the researcher suspects this is due to poor management of the school environment and school culture. Therefore, research is deemed necessary to verify this. This study used a survey method with a quantitative approach, along with correlational and regression techniques. Data collection was conducted through a Likert-scale questionnaire with 47 respondents, who were teachers at State Special Schools in Kuningan Regency. The data analysis results indicate that (1) School environmental management impacts teacher work discipline, (2) School culture impacts teacher work discipline, and (3) School environmental management and school culture jointly impact teacher work discipline. This study recommends improved planning in school environmental management, including the development of more targeted programs and budgets. Organizational skills also need to be improved by clarifying job descriptions and providing better direction to teachers. School culture needs to be strengthened by enforcing clear rules of conduct, educational quality values, and norms. These improvements can help build a more conducive school environment for teachers to carry out their duties with discipline and enthusiasm.